Projecting loan demand from small farmers and fishers in the Philippines - Geoffrey M. Ducanes (Philippine Institute for Development Studies (PIDS), 2020)
Increasing productivity among small farmers and fisherfolk (SFF) is important if the country is to further reduce poverty. In 2019, the AFF sector accounted for 9.2 percent of GDP and slightly less than a fourth of total employment, but still accounted for majority of the poor. The provision of financing SFF is one of the strategies highlighted in the Philippine Development Plan 2017-2022 to expand economic opportunities in agriculture, forestry, and fisheries (AFF). This study develops and applies a method for estimating loan demand from small farmers and small fishers in the Philippines, and projects this demand into the future. The method uses a patchwork of data, but most importantly the Small Farmers and Fisherfolk Indebtedness Survey and the Registry System for Basic Sectors in Agriculture to estimate credit loan demand from SFF in 2017, and uses inflation and projected (or targeted) sectoral gross value-added growth to project SFF loan demand into the future. The loan demand for SFF is estimated to be from Php172 billion (low estimate) to Php367 billion (high estimate) in 2021. This is projected to grow to Php201 billion (low estimate) to Php431 billion (high estimate) in 2024. Moving forward, the study suggests that the estimation of loan demand from SFF can be facilitated if the sampling design of the SFFIS can be revised so as to be made representative nationally (and possibly even by region) using the most recent Census of Agriculture and Fishers as the sampling frame. To help small farmers and fisherfolk, the government should ensure there is adequate fund, whether from government or from formal private sources, to meet the loan demand of small farmers and fishers for purposes of production, while still maintaining prudence. Not only will this help small farmers and fishers keep their head above poverty, it would help boost food security in the country in the present time when there are continuing risks of supply chain disruptions.
Keywords: 330; small farmers and fishers; credit demand estimation; credit demand projection; determinants of credit demand; logit regression; agricultural credit; COVID-19 impact on credit demand